2012
DOI: 10.1038/nrmicro2750
|View full text |Cite
|
Sign up to set email alerts
|

New insights into bacterial adaptation through in vivo and in silico experimental evolution

Abstract: Microbiology research has recently undergone major developments that have led to great progress towards obtaining an integrated view of microbial cell function. Microbial genetics, high-throughput technologies and systems biology have all provided an improved understanding of the structure and function of bacterial genomes and cellular networks. However, integrated evolutionary perspectives are needed to relate the dynamics of adaptive changes to the phenotypic and genotypic landscapes of living organisms. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
164
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 150 publications
5
164
0
Order By: Relevance
“…Some studies have found that E. coli evolved at stressfully high temperature tend to restore their overall gene expression profiles toward the baseline levels corresponding to their ancestor when it is grown the optimal growth temperature of 37°C (49,50). This finding fits with the overall prominence of mutations in global regulatory processes in laboratory evolution experiments with microbes (51), including the LTEE (52).…”
Section: Discussionsupporting
confidence: 55%
“…Some studies have found that E. coli evolved at stressfully high temperature tend to restore their overall gene expression profiles toward the baseline levels corresponding to their ancestor when it is grown the optimal growth temperature of 37°C (49,50). This finding fits with the overall prominence of mutations in global regulatory processes in laboratory evolution experiments with microbes (51), including the LTEE (52).…”
Section: Discussionsupporting
confidence: 55%
“…Note that mere changes in metabolite concentrations are not counted in this picture. RNA-chip studies have also revealed that the expression of many genes can be jointly altered by simple genetic changes, e.g., gene deletions (Wagner 2002) or single fixed mutations in experimental evolution (reviewed in Hindré et al 2012). …”
Section: Practical Illustrationsmentioning
confidence: 99%
“…The relative simplicity of microbial systems, their capacity for rapid evolutionary change, and advances in technology that enable detailed genotypic traceability offer a unique opportunity to log moment-by-moment change in experimental populations, with the potential to contribute to understanding of how genotype shapes phenotype, how phenotype interplays with the environment, and how environment may shape genotype (Mortlock 1982;Lenski et al 1998;Rainey et al 2000;Beaumont et al 2009;Buckling et al 2009;Blount et al 2012;Hindré et al 2012). In the context of adaptive radiation, the bacterium Pseudomonas fluorescens SBW25 has served as a useful model (reviewed within MacLean 2005 andKassen 2009).…”
mentioning
confidence: 99%